Apoptin as a Tumor-Specific Therapeutic Agent: Current Perspective on Mechanism of Action and Delivery Systems - Malla, Waseem Akram; Arora, Richa; Khan, Raja Ishaq Nabi; Mahajan, Sonalika; Tiwari, Ashok Kumar (Frontiers in Cell and Developmental Biology, 2020)
Cancer remains one of the leading causes of death worldwide in humans and animals. Conventional treatment regimens often fail to produce the desired outcome due to disturbances in cell physiology that arise during the process of transformation. Additionally, development of treatment regimens with no or minimum side-effects is one of the thrust areas of modern cancer research. Oncolytic viral gene therapy employs certain viral genes which on ectopic expression find and selectively destroy malignant cells, thereby achieving tumour cell death without harming the normal cells in the neighbourhood. Apoptin, encoded by Chicken Infectious Anaemia Virus’ VP3 gene, is a proline-rich protein capable of inducing apoptosis in cancer cells in a selective manner. In normal cells, the filamentous Apoptin becomes aggregated towards the cell margins, but is eventually degraded by proteasomes without harming the cells. In malignant cells, after activation by phosphorylation by a cancer cell-specific kinase whose identity is disputed, Apoptin accumulates in the nucleus, undergoes aggregation to form multimers and prevents the dividing cancer cells from repairing their DNA lesions, thereby forcing them to undergo apoptosis. In this review, we will discuss the present knowledge about the structure of Apoptin protein, elaborate on its mechanism of action and summarise various strategies that have been used to deliver it as an anticancer drug in various cancer models.